Preclinical research and development of a herbal antipyretic drug based on leaves of Ceiba pentandra (Malvaceae) - Silue, Awa Nounaferi Gnieneferetien; Djadji, Lenoir Thierry Ayoman; Kouakou, Landry S.; Siransy-Kouakou, Gisele N’doua (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Faced with the limits of synthetic antipyretic substances, in particular their involvement in the occurrence of numerous and often serious adverse effects; the challenge is in search of new antipyretics especially from the African traditional pharmacopoeia. The objective of this study was to evaluate the antipyretic activity of an aqueous extract and a formulation of Ceiba pentandra, with a view to designing an herbal antipyretic drug. Methods: Trials of formulation of an antipyretic syrup with leaves extract of Ceiba pentandra were carried out. The antipyretic activity was investigated by the bewer’s yeast induced pyrexia. Physicochemical and microbiological stability tests were carried out on the syrup. Results: It was found with the extract an antipyretic activity at doses of 125 mg/kg and 150 mg/kg. The effect was greater for the 125 mg/kg dose with inhibition percentages ranging from 27.58% to 71.25%. This antipyretic activity was early (from 30 minutes) and was preserved during the four hours of the experiment. The syrup dosed at 125 mg/kg gave an activity similar to that of the extract by significantly reducing the hyperthermia in the rats. Regarding the stability tests, the syrup remained stable both physico-chemically and microbiologically throughout the study period (28 days) both when exposed to low temperature (5 °±3 ° C) and at high temperature (40°±2° C). Conclusions: Ceiba pentandra leaves have antipyretic activity and could be used for the development of an herbal antipyretic drug.